INNOVATIVE STRATEGIES IN THE MANAGEMENT OF COMPLETE EDENTULISM: DIGITAL TECHNOLOGIES, BIOACTIVE BIOMATERIALS, AND PATIENT-CENTERED APPROACHES (Uzbekistan Open Conference, 2025)
Complete edentulism, defined as the loss of all natural teeth in one or both jaws, remains a significant dental and public health challenge worldwide. According to the World Health Organization (WHO), 30–40% of individuals over the age of 65 experience edentulism. This condition negatively impacts chewing efficiency, speech, esthetics, psychological well-being, and social adaptation. In Uzbekistan, complete edentulism is also widespread, with conventional acrylic dentures being the most common treatment option. However, their limited retention, stability, and functional efficiency result in low patient satisfaction.Recent advances in prosthodontics include implant-supported prostheses, digital workflows (CAD/CAM, 3D printing, intraoral scanning), and bioactive biomaterials. This study aimed to evaluate the clinical effectiveness of these innovative strategies compared to conventional dentures. A randomized clinical trial involving 60 edentulous patients was conducted. Results demonstrated that implant-supported overdentures provided superior outcomes in chewing efficiency, occlusal force, and patient satisfaction, while CAD/CAM dentures showed significant advantages in precision and esthetics. Bioactive biomaterials demonstrated promising potential for improving prosthesis biocompatibility and longevity.